Antibacterial Activity and CO2 Capture by Cerium-Copper Mixed Oxides Prepared Using a Co-precipitation Method - Kamonwannasit, Sirilak; Futalan, Cybelle Morales; Khemthong, Pongtanawat; Youngjan, Saran; Phatai, Piaw (Indonesian Journal of Chemistry, 2024)
Indoor air pollution is comprised of fine particles, bacteria, fungi, and hydrocarbons. Acceptable indoor air quality is maintained using several layers of air filters. Alternative materials with the capacity to remove CO2 from indoor air with antibacterial efficacy need to be further investigated. Mixed oxides of Ce1.0-xCuxO (x = 0.0, 0.1, 0.5, 0.9, 1.0) were synthesized using a co-precipitation method. Characterization studies revealed that single oxides of Ce1.0O and Cu1.0O were of cubic fluorite and monoclinic crystal structures, respectively. Results also show that Ce0.1Cu0.9O and Ce0.5Cu0.5O were composites. All samples were classified as mesoporous materials with a type IV isotherm, and the main functional group was identified as Ce–O–Cu. The surface area of Ce0.5Cu0.5O was 17.63 m2/g. The highest CO2 adsorption capacity was 5.72 cm3/g for Ce0.5Cu0.5O. Moreover, the greatest antibacterial activity against B. subtilis (12.22 mm inhibition zone) and P. aeruginosa (7.34 mm inhibition zone) was observed for Ce0.5Cu0.5O at a 30 mg/L concentration. The synthesis of mixed Ce1.0-xCuxO oxides along with their satisfactory antibacterial performance and CO2 adsorption capacity, indicate its potential use as an alternative material for inclusion in indoor air filters.